The UN’s’ Development Goals, the AACSB, and the Political Economy of Illusion - Wagner, Richard E. (European Scientific Journal, ESJ, 2023)
In 1903 the Italian economist Amilcare Puviani articulated a theory of fiscal illusion to promote better understanding of the course of political action. Puviani created his theory to explain the failure of political pronouncements to reflect the reality to which those pronouncements claimed to pertain. Several commentators have since amplified Puviani’s recognition that political action operates through fomenting illusion within the citizenry. In contemporary times, the United Nations has articulated 17 pleasant sounding goals for global development. Further, the Association to Advance Collegiate Schools of Business (AACSB) amplifies the UN in insisting that business schools incorporate those development goals into their curricula. After describing the theory of fiscal illusion, this essay explains how the AACSB’s promotion of the UN’s development goals provides a case study of the bureaucratic imperative which both the AACSB and the UN reflect, and with that imperative illustrating the political economy of fiscal illusion.